Eleanor Zelliot y Maxine Berntsen (eds.), The Experience of Hinduism. Essays on Religion in Maharashtra, Nueva York, State University of New York Press, 1988, 387 pp. - Duque Peláez, Isabel A. (Estudios de Asia y África, 1989)
-